Taxation and Incentive in Mobilization: Reply - Cooper, Gershon (Quarterly Journal of Economics, 1952)
Taxation and Incentive in Mobilization: Reply Get access Gershon Cooper Gershon Cooper The RAND Corporation, Santa Monica, California Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 66, Issue 4, November 1952, Pages 609–613, https://doi.org/10.2307/1882112 Published: 01 November 1952